Development of digital intelligent networked manufacturing for flexible customized manufacturing - Zhongde SHAN; Jun WANG; Qian ZHANG (物联网学报)
Digital intelligent networked manufacturing technology and equipment are important foundations for the construction of manufacturing power and Internet power.They are important tools for the construction of digital workshop and intelligent factory, enabling the transformation and upgrading and high-quality development of the manufacturing industry.Combined with the characteristics of multiple varieties and variable batches of products in the aerospace field, it was studied how to better conduct digital intelligent networked manufacturing, how to better build digital manufacturing workshops and flexible intelligent manufacturing factories.For single piece and small batch flexible manufacturing, the construction principle, implementation path and technical architecture of digital intelligent flexible manufacturing production line and workshop/factory were proposed, which could be used to guide the construction of digital intelligent workshop/factory for future flexible manufacturing standardization.Through the exploration and application practice of typical intelligent factory construction in the aerospace field, the innovative scenario applications were explored, such as flexible intelligent production equipment, automatic flexible precision measurement equipment, measurement feedback-based adaptive processing and industrial internet-based digital twin system.